The Marketing Strategy of Pink Label Sexy Dancer in Yogyakarta Entertainment - , TYAS PINTAKA DEWI, Tri Nuraniwati, SS, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper aims to explain the purpose of Pink Label marketing. There are several ways to get data of Pink Labelâs actions in its mission to get its vision by using concepts of STP analysis and SWOT analysis. Some methods of collecting data are direct observation, interviews, and library research. Direct observation is conducted intensively three months in order to know how their programs that works to stay alive in their market. Interviewing the leader, members and ex members of Pink Label is useful to get the valid information. Meanwhile, the library research is done to collect some additional information to support the discussion of this paper. Acording to the STP and SWOT analysis, Pink Labelâs development is influenced by several matters. Based on STP analysis, Pink Labelâs sexy appearance supports Pink Labelâs character, so Pink Label is easier in its positioning process. Pink Labelâs dancers who have more than one responsibility makes Pink Label cannot focus on its growth. It makes Pink Label difficult to develop the operational. All that matters above would be related to the vision and mission. How good Pink Label works the missions, if the vision is circumscribed